Cell immobilization for cyclodextrin production: Mini review - Nurul Nabila Huda, Baharudin; Rohaida, Che Man; Nur Hasmaliana, Abdul Manas; Rabi’atul Adawiyah, Ahmad; Nur Nadia, Mohd Zakaria (Penerbit Universiti Teknologi Malaysia, 2023)
Cell immobilization has been applied in various industries, including chemical manufacturing, food, pharmaceutical, and textile. Recently, innovations in cell immobilization techniques and support materials have been put forward for application in high value-added chemical biosynthesis, such as cyclodextrin (CD). The techniques, support materials, and process parameters of cell immobilization play important roles in achieving high CD yield. This review should help one choose the correct cell immobilization technique and support for a CD biosynthesis setup. Previously, CD biosynthesis utilized free cells, even though they present difficulties such as the low product yield, cell lysis, unstable plasmid, and non-reusable cells. This review highlights how the problems that arise from free-cell bioreactors could be mitigated by cell immobilization. The process conditions of cell immobilization for CD production are also presented.